PENGARUH STRUKTUR MODAL, KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN DIVIDEN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Sinaga, Irma Suryani; Munthe, Kornel (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2023)
The aim of this research is to determine and explain the influence of capital structure, institutional ownership, dividend policy and company growth on share prices in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period, both simultaneously and partially. This research focuses on manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period, totaling 179 companies. By using the purposive sampling method, a sample of 34 companies was obtained. The analysis technique used is a multiple linear regression model with descriptive statistical tests, classical assumption tests, and hypothesis testing. The research results show that capital structure and institutional ownership have a negative and insignificant effect on share prices, dividend policy and company growth have a positive and significant effect on share prices.